دور الألعاب الحركية الموجهة في تنمية التفكير الابداعي لدى أطف ال الروضة *رياض الأطف ال بولاية الأغواط - عبد القادر كروم; هواري بوشهير (My University, 2022)
This study aims to identify the role of directed kinetic games in developing creative thinking among kindergarten children. . The results of this study indicated an improvement in the level of development of creative thinking, which is attributed to the role of directed kinetic games with the presence of statistically significant differences between the two groups, which affects all variables and in favor of the experimental group.